Consumers’ Buying Decision Factors toward Second - Hand Clothes in Bangkok - Tubpadung, Sinfah (Community and Social Development Journal, 2018)
Abstract The objectives of this study were to study the relationship of marketing mix, effect of motivation, social influences and impact of attitudes those affect consumers’ decision to buy second hand clothes in Bangkok. This research is a survey research useing questionnaires as data collective tools creating from the related literatures review. The target group in this study were consumers who used to buy second-hand clothes in Bangkok metropolitan area. From Taro Yamane Formula target group was 400 people. The sampling methods had 2 steps : simple random samplings and quota sampling. The hypothesis was tested by the multiple regression. The research findings were as follows: Most of the samples were female, between the ages of 15 and 24 with monthly income. 10,000-19,999 baht. The highest education level is mostly under the bachelor. The external motivation in the marketing mix found that the overall was at the high level. And the social impact factors were found to be in the moderate level. The internal motivation in the reasonable factors found that the overall was at the high level. And the emotional factors were found to be in the moderate level. The attitudes factors were found to be in the moderate level. The buying decision factors were found to be in the moderate level. The hypothesis results were that external motivation; internal motivation and attitude were affective to customers’ buying decision factors about buying second-hand cloths in Bangkok.